Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs

Understanding endothelial dysfunction in diabetic cardiovascular complications using mass spectrometry-based proteomics - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kazi, Rubina; Kulkarni, Mahesh J. (Heart, 2016)

Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

Advanced glycation end products modulate amyloidogenic APP processing and tau phosphorylation: a mechanistic link between glycation and the development of alzheimer's disease - Batkulwar, Kedar; Godbole, Rashmi; Banarjee, Reema; Kassaar, Omar; Williams, Robert J.; Kulkarni, Mahesh J. (ACS Chemical Neuroscience, 2018)
Advanced glycation end products (AGEs) are implicated in the pathology of Alzheimer's disease (AD), as they induce neurodegeneration following interaction with the receptor for AGE (RAGE). This study aimed to establish a mechanistic link between AGE-RAGE signaling and AD pathology. AGE-induced changes in the neuro2a proteome were monitored by SWATH-MS. Western blotting and cell-based reporter assays were used to investigate AGE-RAGE regulated APP processing and tau phosphorylation in primary cortical neurons. Selected protein expression was validated in brain samples affected by AD. The AGE-RAGE axis altered proteome included increased expression of cathepsin B and asparagine endopeptidase (AEP), which mediated an increase in A beta(1-)(42) formation and tau phosphorylation, respectively. Elevated cathepsin B, AEP, RAGE, and pTau levels were found in human AD brain, coincident with enhanced AGEs. This study demonstrates that the AGE-RAGE axis regulates A beta(1-)(42) formation and tau phosphorylation via increased cathepsin B and AEP, providing a new molecular link between AGEs and AD pathology.

Proteomic study of endothelial dysfunction induced by Ages and its possible role in diabetic cardiovascular complications - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kulkarni, Mahesh J. (Journal of Proteomics, 2018)
Endothelial dysfunction is one of the primary steps in the development of diabetes associated cardiovascular diseases. Hyperglycemic condition in diabetes promotes accumulation of advanced glycation end products (AGEs) in the plasma, that interact with the receptor for AGEs (RAGE) present on the endothelial cells and negatively affect their function. Using Human umbilical vascular endothelial cells (HUVECs) in culture, the effect of glycated human serum albumin on global proteomic changes was studied by SWATH-MS, a label free quantitative proteomic approach. Out of the 1860 proteins identified, 161 showed higher abundance while 123 showed lesser abundance in cells treated with glycated HSA. Bioinformatic analysis revealed that the differentially regulated proteins were involved in various processes such as apoptosis, oxidative stress etc. that are associated with endothelial dysfunction. Furthermore, the iRegulon analysis and immunofuorescence studies indicated that several of the differentially regulated proteins were transcriptionally regulated by NF-kappa B, that is downstream to AGE-RAGE axis. Some of the important differentially regulated proteins include ICAM1, vWF, PAI-1 that affect important endothelial functions like cell adhesion and blood coagulation. qPCR analysis showed an increase in expression of the AGE receptor RAGE along with other genes involved in endothelial function. AGE treatment to HUVEC cells led to increased oxidative stress and apoptosis. This is the first proteomics study that provides insight into proteomic changes downstream to AGE-RAGE axis leading to endothelial dysfunction and predisposing to cardiovascular complications. Significance: Cardiovascular disease (CVD) is a major pathological outcome in diabetic patients and it is important to address ways that target its development before the onset. Elevated plasma AGEs in diabetes can affect endothelial function and can continue to show their effects even after blood glucose levels are back to normal. Since endothelial dysfunction acts as one of the initiating factors for the development of CVD, understanding how AGEs affect the endothelial cell proteome to cause dysfunction will provide insight into the mechanisms involved and aid designing new therapeutic approaches.

CD44, a predominant protein in methylglyoxal-induced secretome of muscle cells, is elevated in diabetic plasma - Bai, Shakuntala; Chaurasiya, Arvindkumar H.; Banarjee, Reema; Walke, Prachi B.; Rashid, Faraz; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2020)
Methylglyoxal (MG), a glycolytic intermediate and reactive dicarbonyl, is responsible for exacerbation of insulin resistance and diabetic complication. In this study, NIG-induced secretome of rat muscle cells was identified and relatively quantified by SWATH-MS. A total of 643 proteins were identified in MG induced' secretome, of which 82 proteins were upregulated and 99 proteins were downregulated by more than 1.3-fold in SWATH analysis. Further, secretory proteins from the dassical secretory pathway and nonclassical secretory pathway were identified using SignalP and SecretomeP, respectively. A total of 180 proteins were identified with SignalP, and 113 proteins were identified with SecretomeP. The differentially expressed proteins were functionallyannotated by KEGG pathway analysis using Cytoscape soft ware with plugin clusterMaker. The differentially expressed proteins were'sfound to he involved m various pathways like extracellular matrix (ECM) receptor interaction, leukocyte transendothelial migration, fluid shear tress and atherosclerosis, complement and coagulation cascades, and lysosomal pathway. Since the MG levels are high in diabetic conditions, the presence of MG-induced isecreted proteins was inspected `by profiling human plasma of healthy and diabetic subjects (n = 10 each). CD44, a predominant MG -induced secreted protein, was found to be elevated in the diabetic plasma and to have a role in the development of insulin resistance.

Enzymatic and non-enzymatic detoxification of reactive carbonyl compounds improves the oxidative stress tolerance in cucumber, tobacco and rice seedlings - Nareshkumar, Ambekar; Subbarao, Sindhu; Vennapusa, Amarnatha Reddy; Ashwin, Vargheese; Banarjee, Reema; Kulkarni, Mahesh J.; Ramu, Vemanna S.; Udayakumar, Makarla (Journal of Plant Growth Regulation, 2020)
Detoxification of reactive carbonyl compounds (RCC) is crucial to sustain cellular activity to improve plant growth and development. Seedling growth is highly affected by accumulation of RCC under stress. We report non-enzymatic, enzymatic mechanisms of detoxification of RCC in the cucumber, tobacco and rice seedling systems exposed to glucose, NaCl, methyl viologen (MV) induced oxidative stress. The cucumber seedlings exposed to carbonyl stress had higher levels of malondialdehyde (MDA), protein carbonyls (PCs) and advanced glycation end-product N-carboxymethyl-lysine (AGE-CML) that negatively affected the seedling growth. The overexpression of enzyme encoding aldo-keto reductase-1 (AKR1) in tobacco and rice showed detoxification of RCC, MDA and methylglyoxal (MG) with improved seedling growth under glucose, NaCl and MV-induced oxidative stress. Further, small molecules like acetylsalicylic acid (ASA), aminoguanidine (AG), carnosine (Car), curcumin (Cur) and pyridoxamine (PM) showed detoxification of RCC non-enzymatically and rescued the cucumber seedling growth from glucose, NaCl and MV-stress. In autotrophically grown rice seedlings these molecules substantially improved seedling growth under MV-induced oxidative stress. Seedlings treated with the small molecules sustained higher guaiacol peroxidase (GPX) enzyme activity signifying the role of small molecules in reducing carbonyl stress-induced protein inactivation and AGE-CML protein modifications. The results showed that besides enzymatic detoxification of RCC, the small molecules also could reduce cytotoxic effect of RCC under stress. The study demonstrates that small molecules are attractive compounds to improve the seedling growth under stress conditions.
Keywords: Oxidative stress; plant growth; Reactive carbonyl scavengers; Seed germination; small molecules

Plasma-derived extracellular vesicles reveal galectin-3 binding protein as potential biomarker for early detection of glioma - Rana, Rashmi; Chauhan, Kirti; Gautam, Poonam; Kulkarni, Mahesh; Banarjee, Reema; Chugh, Parul; Chhabra, Satnam Singh; Acharya, Rajesh; Kalra, Samir Kumar; Gupta, Anshul; Jain, Sunila; Ganguly, Nirmal Kumar (Frontiers in Oncology, 2021)
{Gliomas are the most common type of the malignant brain tumor, which arise from glial cells. They make up about 40% of all primary brain tumors and around 70% of all primary malignant brain tumors. They can occur anywhere in the central nervous system (CNS) and have a poor prognosis. The average survival of glioma patients is approximately 6-15 months with poor aspects of life. In this edge, identification of proteins secreted by cancer cells is of special interest because it may provide a better understanding of tumor progression and provide early diagnosis of the diseases. Extracellular vesicles (EVs) were isolated from pooled plasma of healthy controls (n=03) and patients with different grades of glioma (Grade I or II or III
Keywords: blood-based biomarker; early detection; galectin-3 binding protein; plasma-derived extracellular vesicles; proteomics

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry